Highly Efficient Phase Boundary Biocatalysis with Enzymogel Nanoparticles1. Issue 2 (8th November 2013) - Kudina, Olena; Zakharchenko, Andrey; Trotsenko, Oleksandr; Tokarev, Alexander; Ionov, Leonid; Stoychev, Georgi; Puretskiy, Nikolay; Pryor, Scott W.; Voronov, Andriy; Minko, Sergiy
Abstract The enzymogel nanoparticle made of a magnetic core and polymer brush shell demonstrates a novel type of remote controlled phase‐boundary biocatalysis that involves remotely directed binding to and engulfing insoluble substrates, high mobility, and stability of the catalytic centers. The mobile enzymes reside in the polymer brush scaffold and shuttle between the enzymogel interior and surface of the engulfed substrate in the bioconversion process. Biocatalytic activity of the mobile enzymes is preserved in the enzymogel while the brush‐like architecture favors the efficient interfacial interaction when the enzymogel spreads over the substrate and extends substantially the reaction area as compared with rigid particles.